Euroscepticism: A Mobilising Appeal? Not for Everyone! - Gyárfášová Olga (Sciendo, 2015)
This study examines the changing role of the EU agenda in Slovak politics. It identifies old and newly emerging faces of Euroscepticism and compares them with general theoretical concepts. Furthermore, it asks to what extent Eurosceptical appeals mobilised Slovak voters in the European Parliament (EP) elections of 2014 and whether Eurosceptical parties represent a meaningful electoral choice for voters. In the past, many analyses have provided evidence that the European agenda is not salient and the EU political arena is perceived as one where there is less at stake. Nevertheless, the economic crisis and so-called Greek bailout were followed by a rise in Euroscepticism and EU-criticism. In some EU countries, this enhanced voter mobilisation in the EP elections. In others – including Slovakia – we saw not only a significant decline in electoral turnout but relatively poor results for Eurosceptical parties as well. This study identifies the factors behind abstention and explores voting patterns in this specific second-order election in Slovakia. Moreover, it investigates how the parties are perceived in terms of their positions on EU integration and the potential impact on voter choices. I conclude that the EU agenda is still not the deciding factor for voters even in the case of EP elections. Eurosceptical appeals are less mobilising in this context, and the public sees no differences among parties’ stances on the EU.